A valoração do enfermeiro sobre o cuidado de enfermagem prestado no serviço pré-hospitalar de urgência e emergência - Grazielli Fabiana Gava (2020)
This research has as object of study the evaluation given by nurses on nursing care before the patient treated in the prehospital mobile urgency and emergency service. Nursing is a scientific and social practice. Analyzing it as a social practice, it is perceived its insertion in the axiological field. Thus, end of values that give it meaning and sense. Their experience allows the rescuer-nurse to reflect and shape him as a person, enabling his referral to a human act. It is undoubted that the professional action of nurses is expressed by nursing care. Thus, in the work, he was uneasy about restricting care to the biological and technical dimension, ignoring the complexity that foundations human life. The theoretical beacon of this study is centered on Max Scheler's thinking of value theory. The objectives of this research were: to identify the values assumed by nurses in the urgency and emergency prehospital mobile service that merge nursing care; and to understand, Max Scheler's thinking, the values that guide the nursing care assumed by nurses in the prehospital urgency and emergency mobile service. The qualitative methodology was adopted, with phenomenological approach. The study was develop in the urgency and emergency mobile prehospital service, maintained by the Intermunicipal Consortium of the Southeast Macroregion (CISDESTE), located in Minas Gerais - MG. The subjects were the nurses working in an advanced life support unit of that service. For data collection, we opted for a convenience sample with six participants, who gave their statements through interviews, which were recorded and stored in electronic archive. The inclusion criterion was to be rescuer-nurse, with a minimum working time of twenty-four months in the service; and the exclusion rescuer-nurse was the first responder nurse crowded in the service and not working in the advanced support unit. Data collection took place from April, 2019. The semi-structured interview having as a guiding question: "How do you emphasize nursing care to the patient in the mobile prehospital urgency and emergency service?". The analysis and interpretation of the data was performed through the Dilthey’s hermeneutics, with an exhaustive rereading of the interviews to capture the values from the interviewees' statements. This study met the ethical precepts required by CNS Resolutions 466/2012 and 580/2018. Three values were identified in the discourses of rescuers-nurses, according to schelerian precepts: social value, useful value and logical value. The data were categorized in order to present and relate the value/ care of nursing. The first category was "Nursing care and social value: concern for the other". In it, the nurse highlights the concern with the other as a duty-being for nursing care and thus commits to the other, giving him attention. The first-rate nurse made the Eu-Tu relationship emerge in the praxis, causing nursing care to be recognized as the holder of primary consideration, knowledge, love and concern. It was a moral obligation, which conferred the pragmatic professional sense and, the value of the patient as a person was rediscovered, from nursing care. The second category was "Nursing care and useful value: the art of nursing", in which care manifests itself by nursing techniques, as art, but it is not restricted to it. In such a way, for the exercise of nursing art, the first responder nurse must develop three basic competencies, they are: the know how to think, know how to do and know how to live. He admitted that the nursing technique was allied with ethical commitment and scientific competence. Thus, nursing care is something greater than useful value. This value does not end the making of the profession. For the rescuer-nurse, the technique was mediator, because it allowed the approach with the patient and, with this, he was able to listen to him, to take him in a humanized manner. The last category presented was "Nursing care and logical value: learning to learn", in which scientific knowledge is necessary for the rescuer-nurse to perform care in their practice, since it was educated in the culture that privileges the use of reason, tending to establish its pragmatic guided by this spirit of research and scientificity. At the end of this research, it can be affirmed that, for the rescuer-nurse, nursing care is humanized, conscious, supportive, useful, ethical, scientific and holistic and is necessary for the profession to be ratified as science and recognized as such. This care is relevant for the patient in the various contexts of health and disease that mark human life, constituting the essence of the profession.